Exploring the hidden treasures: Deep-sea bacterial community structure in the Bay of Bengal and their metabolic profile - Verma, Pankaj; Pandey, Vikas; Seleyi, Seyieleno C.; Alagarsamy, Abirami; Dharani, Gopal (Frontiers in Marine Science, 2024)
Deep sea bacterial communities demonstrate remarkable adaptability to high-pressure environments coupled with low temperatures which has sparked curiosity about their diversity and exceptional metabolic pathways. Additionally, bacteria in the deep sea exert a substantial influence over various biogeochemical processes. To date, we have relatively very little information about the deep-sea bacterial communities and, they remain largely unexplored. We investigated the variability in the physicochemical conditions, heavy metals and their influence on deep-sea bacterial community structure across three different depths in the Bay of Bengal. The structural and metabolic diversity of deep-sea sediment microbial communities were examined through culture-based sequencing of 16S rRNA genes, ecto-enzymatic studies, and community-level physiological profiling. Bacillota was the most dominant phylum representing 61% of the cultured bacterial isolates, while the remaining belonged to Actinomycetota and Pseudomonodata. Five potential novel species belonging to the genera Fictibacillus, Lysinibacillus, Salinicola, Robertmurraya and Blastococcus were identified. The extracellular enzymatic activity was positive for >50% of the bacterial isolates, wherein the genera Bacillus and Micromonospora exhibited versatile profiles. High metabolic diversity was recorded through the carbon substrate utilization profiles indicating that microbial communities are active participants in biogeochemical cycles in the deep sea. The most prominently utilized carbon substrates were α-cyclodextrin, glucose-1-phosphate, D-xylose, glycogen, and 2-hydroxy benzoic acid which serve as organic substrates for microbial metabolism, facilitating the decomposition of organic matter and, recycling carbon in deep-sea ecosystems. Multivariate statistical analyses confirmed that the environmental variables had a profound influence on the bacterial community. The findings shed light on spatial variability in the bacterial community structure, enzyme activity and metabolic profiles, and enhance our understanding of Bay of Bengal deep-sea sedimentary microbial ecology.